Impact of Climate Change on Rice and Wheat Adaptation Strategies and resource conservation measures - Prakash, Ved; Kumar, Santosh; Dwivedi, S K; Mishra, J S (Indian Farming, 2017)
Climate change and increase in temperature over the years has adverse effect on rice and wheat crops. It is therefore necessary to follow adaption strategies and resource conservation measures for growing these crops.